Accounting for the cyclical dynamics of income shares - Enchuan Shao; Pedro Silos (Federal Reserve Bank of Atlanta, 2011)
Over the business cycle, labor's share of output is negatively but weakly correlated with output, and it lags output by about four quarters. Profit's share is strongly procyclical. It neither leads nor lags output, and its volatility is about four times that of output. Despite the importance of understanding the dynamics of income shares for understanding aggregate technology and the degree of competition in factor markets, macroeconomics lacks models that can account for these dynamics. This paper constructs a model that can replicate those facts. We introduce costly entry of firms in a model with frictional labor markets and find a link between the ability of the model to replicate income shares' dynamics and the ability of the model to amplify and propagate shocks. That link is a countercyclical real interest rate, a well-known fact in U.S. data but a feature that models of aggregate fluctuations have had difficulty achieving.
Keywords: E3; E25; J3; E24; 330; labor's share; frictional labor market; firm entry